(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the quality of life of hemiplegia patients after stroke at Ha Dong General Hospital in 2023-2024. Method: Cross-sectional study. Results: The study was conducted on 40 patients being treated for stroke at the Department of Internal Medicine and Department of Cardiology of Ha Dong General Hospital. The study used the stroke specific quality of life scale to describe the quality of life of hemiplegia patients after stroke. The results showed that: 25% of patients had good quality of life; 52.5% of patients had average quality of life and 22.5% of patients had poor quality of life. Conclusions: The proportion of patients with average and poor quality of life is high. Therefore, it is necessary to have active and specific measures in the care and treatment process to contribute to improving and enhancing the quality of life for patientsfor patients.